Upregulated lncARAT in Schwann cells promotes axonal regeneration by recruiting and activating proregenerative macrophages - Gang Yin; Yaofa Lin; Peilin Wang; Jun Zhou; Haodong Lin (BMC, 2022)
Abstract Background Axonal regeneration following peripheral nerve injury (PNI) depends on the complex interaction between Schwann cells (SCs) and macrophages, but the mechanisms underlying macrophage recruitment and activation in axonal regeneration remain unclear. Methods RNA sequencing (RNA-seq) was conducted to identify differentially expressed long noncoding RNAs (DElncRNAs) between crushed sciatic nerves and intact contralateral nerves. The putative role of lncRNAs in nerve regeneration was analyzed in vitro and in vivo. Results An lncRNA, called axon regeneration-associated transcript (lncARAT), was upregulated in SCs and SC-derived exosomes (SCs-Exo) after sciatic nerve injury. LncARAT contributed to axonal regeneration and improved motor function recovery. Mechanistically, lncARAT epigenetically activated C-C motif ligand 2 (CCL2) expression by recruiting KMT2A to CCL2 promoter, resulting in increased histone 3 lysine 4 trimethylation (H3K4me3) and CCL2 transcription in SCs. CCL2 facilitated the infiltration of macrophages into the injured nerves. Meanwhile, lncARAT-enriched exosomes were released from SCs and incorporated into macrophages. LncARAT functioned as an endogenous sponge to adsorb miRNA-329-5p in macrophages, resulting in increased suppressor of cytokine signaling (SOCS) 2 expression, which induced a proregenerative function of macrophages through a signal transducer and activator of transcription (STAT) 1/6-dependent pathway. Conclusions LncARAT may represent a promising therapeutic avenue for peripheral nerve repair.